2015
DOI: 10.1111/and.12421
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and anti-apoptotic effects ofSatureja khuzestanicaessential oil against busulfan-mediated sperm damage and seminiferous tubules destruction in adult male mice

Abstract: We studied the protective effect of Satureja khuzestanica essential oil (SKEO) against damage caused by busulfan on testis in male mice. The NMRI mice (n = 40) were assigned to four groups including: G1: control, G2: treated with busulfan for 4 days (3.2 mg kg(-1)), G3: receive busulfan (4 days, 3.2 mg kg(-1)) and SKEO (28 days, 225 mg kg(-1)) at the same time, G4: pre-treated with SKEO (7 days, 225 mg kg(-1)) and subsequently cotreated with busulfan (4 days, 3.2 mg kg(-1)) and SKEO (28 days, 225 mg kg(-1)). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…Another study was conducted by Abo-Ghanema et al using the combination of ginger and L-carnitine to treat infertile rats. The authors showed that this combination increased the weight of testicles and seminal vesicles, improved the quality and quantity of semen (33). …”
Section: Discussionmentioning
confidence: 99%
“…Another study was conducted by Abo-Ghanema et al using the combination of ginger and L-carnitine to treat infertile rats. The authors showed that this combination increased the weight of testicles and seminal vesicles, improved the quality and quantity of semen (33). …”
Section: Discussionmentioning
confidence: 99%
“…Busulfan as a widely used cancer therapy agent in chronic diseases such as leukemia, lymphoma, and before bone marrow transplantation, induces temporary or permanent sterility in male patients (Dehghani et al 2013;Hosseini et al 2014). Also, recent reports have shown various adverse effects of busulfan injection on the male reproductive system including oligospermia (Dehghani et al 2013), azoospermia (Panahi et al 2015), low testis weights (Nasimi et al 2016), changes in the serum levels of male sexual hormones (Hosseini et al 2014), increasing apoptotic sperm, inducing oxidative stress, and cytotoxicity (Nasimi et al 2015;Vahdati et al 2015). Thus, sperm as a quickly dividing cell is a greater target for damage by chemotherapy (Meistrich 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies illustrated that oral administration of Satureja Khuzestanica essential oil (SKEO) to rats as a strong anti-oxidant (Abdollahi et al 2003;Ahmadvand et al 2012) confers various biological and pharmacological activities including anti-diabetic, antiatherogenic (Ahmadvand et al 2012), and reproductive stimulatory properties (Assaei et al 2015;Nasimi et al 2016). SKEO also demonstrates a significant increase in leydig cells, spermatozoids, and serum testosterone level in male normal rats (Safarnavadeh and Rastegarpanah 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quality of life and the preservation of fertility have emerged as significant issues [5]. New methods should be developed to prevent testicular damage induced by alkylating agents [6, 7]. …”
Section: Introductionmentioning
confidence: 99%